Temperature induced polytype conversion in cubic silicon carbide studied by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 2004)
In this paper, we study the polytype transformation of cubic silicon carbide (3C-SiC) by micro Raman spectroscopy. Two sets of samples are investigated. First, physical vapor transport (PVT) grown samples, grown on chemical vapor deposition (CVD) substrates at growth temperatures between 1800 and 1950°C. The microscopic images of the cross sections and the Raman spectra taken on these grown crystals show a growing fraction of 6H-SiC inclusions with increasing growth temperature. To decide whether these polytype inclusions are induced by the PVT growth process or by the temperature treatment of the CVD substrates, we studied the temperature induced polytype coversion of cubic CVD substrates grown on undulant Si(100) surfaces which were used as seed crystals for the PVT growth. The CVD substrates were annealed in the temperature range between 1700 and 2100°C. The results of this annealing series are similar to the results we find in the PVT grown samples. Therefore we argue that the polytype conversion is not induced by the PVT growth process but a result of the heat treatment of the CVD seed crystals. © 2004 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.temper